Optimizing the Role of BHABINKAMTIBMAS in Reducing Crime Rates Through Community Policing Strategies in Pasar X Village, Kutalimbaru Subdistrict - Brema Putranta; Rayani Saragih; Maslon Hutabalian (Indonesian Journal of Advanced Research, 2026)
Public order and community security constitute an absolute prerequisite for national development. At the rural scale, such as Pasar X Village in Kutalimbaru District, security stability faces various local crime challenges. This study aims to evaluate the functional role of Bhayangkara Pembina Keamanan dan Ketertiban Masyarakat (Bhabinkamtibmas) in executing community policing strategies to minimize crime rates, while analyzing determinants that affect local legal awareness. This legal-sociological (empirical juridical) research relies on field exploration through systematic observation, statutory documentation, and in-depth interviews with Bhabinkamtibmas officers and village leaders. Data are scrutinized using descriptive-qualitative techniques. The analysis reveals that the operational implementation of Bhabinkamtibmas in Pasar X Village complies with Law No. 2 of 2002 and Indonesian National Police Regulation No. 7 of 2021. Preventative methods are channeled via periodic home visits (sambang), police-community partnership forums (FKPM), and community-based restorative justice. The effectiveness of crime prevention is positively driven by social openness, although bounded by structural vehicle constraints within hilly geographical terrains.